Cooperative Learning Through Online Media to Improving Islamic Religious Education Learning Outcomes of Students at Junior High School - Hasan, Nurmalinda; Rosadi, KemasImron; Hidayat, Hidayat (Zabags International Journal of Education, 2023)
This study aims to provide an analysis of the picture and picture cooperative learning model through online media in improving student learning outcomes of Islamic religious education. The method used is a qualitative approach with data collection techniques in the form of interviews, observation, and documentation. while the data validity testing techniques, namely credibility, transferability, dependability, confirmability, and triangulation. The results of this study, it can be seen that the picture and picture cooperative learning model through online media is a form of teacher control in monitoring students' understanding of the material provided on WhatsApp. In addition, in the zoom meeting there is a feature that can record the learning process, so that teachers and students can look back on the learning videos in the future. The supporting and inhibiting factors of the learning evaluation have a positive impact on student learning outcomes both cognitively affective and psychomotor.